Plasma disposition of danofloxacin 2.5% in goats - Errecalde, Carlos A. (2018)
Pharmacokinetic parameters of danofloxacin at 2.5% were determined after intravenous and intramuscular application in adult goat females. Plasma levels were quantified by HPLC with fluorescence detector set at 295 nm excitation and 490 nm emission using mobile phase composed of water, acetonitrile and triethylamine (79:19:1 v/v/v) adjusted to pH 3.0. In each route of application, using plasma concentrations versus time data in each animal, pharmacokinetic parameters were determined with PK Solution 2.0 software. Quantification limit of the assay was 0.0048 μg/ml. The kinetic profile exhibited by danofloxacin in goats was similar to that of fluoroquinolones in domestic animals. The intramuscular application provides rapid absorption, produces a Cmax of 0.36 ± 0.13 μg/ml at 55.1 ± 13.8 minutes, and exhibits wide distribution in the organism and bioavailability (F) of 109.7 ± 19.8%. Danofloxacin showed a slight permanence in the organism, according to the values obtained in t½β = 4.35 hours (EV), 4.32 hours (IM) and in the TMR = 5.9 hours (EV), 6.7 hours (IM). Intramuscular and intravenous application are comparable, but rational use requires dosage adjustment to ensure clinical and therapeutic success, because plasma Cmax/ MIC90 and ABC/ MIC90 ratios of 9 and 41, respectively in relation to MIC90 of M. haemolytica, are insufficient to ensure clinical-microbiological efficacy.